Silkworm Cocoon—Derived Carbon Dots for Post-Trauma Hemostasis and Tissue Repair - Xinru Wu; Miaomiao Yao; Xuan Qiao; Lintao Li; Zhiyun Meng; Shuchen Liu; Yunbo Sun; Hui Gan; Xiaoxia Zhu; Zhuona Wu; Ruolan Gu; Guifang Dou (Pharmaceuticals)
Background: Traumatic hemorrhage management is challenging due to the need to control severe bleeding and support tissue repair. An ideal material would possess both hemostatic and wound-healing properties. Methods: Silkworm cocoon-derived carbon dots (SC-CDs) were synthesized via a hydrothermal method. After physical and chemical characterization using techniques such as HR-TEM and XPS, their hemostatic efficacy was assessed in rat liver injury, tail transection, and mouse coagulation disorder models. Moreover, the effects of the SC-CDs on platelet aggregation and activation were evaluated. The potential of the SC-CDs to promote wound healing was investigated through cell scratch assays and a mouse full-thickness skin defect model. Results: The SC-CDs showed a high quantum yield (12.9% ± 0.42%), with low hemolytic activity and cytotoxicity. In the hemostasis models, the SC-CDs significantly reduced the bleeding time and volume. In the rat liver injury model, the bleeding time was shortened from 152.67 ± 4.16 s (Control) to 55.33 ± 9.50 s (p < 0.05). In the rat tail transection model, the bleeding volume was reduced from 1.71 ± 0.16 g (Control) to 0.4 ± 0.11 g (p < 0.05). In the mouse coagulation disorder model, an 8 mg/kg dose reduced the bleeding volume to 11.80% ± 0.39% of that of the Control (p < 0.05). Mechanistic studies suggested enhanced platelet activation and aggregation. In the wound healing experiments, the SC-CDs reduced the wound area (88.53 ± 11.78 mm2 (Control) vs. 70.07 ± 6.71 mm2 (SC-CDs), p < 0.05) and promoted fibroblast migration (24 h scratch width: 372.34 ± 9.06 μm (Control) vs. 259.49 ± 36.75 μm (SC-CDs), p < 0.05). Conclusions: SC-CDs show promise for hemorrhage management and tissue regeneration, with potential applications in cases of internal bleeding or coagulation disorders.